MEASUREMENT UNCERTAINTY OF WINDING TEMPERATURE RISE ON WASHING MACHINE HEATING-TEST - Himma Firdaus; Nanang Kusnandar (Instrumentasi, 2021)
Evaluation of measurement uncertainty in safety tests is critical for a testing laboratory, especially if many aspects influence the test results, such as in the washing machine heating test. While performing the heating test, the temperature rise of the motor winding was determined to evaluate the safety level of a washing machine. The temperature rise is obtained by the resistance method, which measures the change of winding resistance to assess its temperature rise. In this work, the washing machine was loaded at maximum capacity and supplied with hot water. All factors contributing to the measurement uncertainty originating from both the measurement system and the testing method are evaluated. The expanded uncertainty of the temperature rise measurement obtained in this study is 1.4%.  This uncertainty is mainly contributed by the variance of test water temperature (0.54%), calibration uncertainty of RCL meter (0.43%), and calibration uncertainty of temperature logging system (DLS) (0.31%). Therefore, the heating test requires a tight temperature controller, an improved calibration uncertainty of the resistance meter, and a better accuracy of the temperature logger to reduce the measurement uncertainty.